Mitigating potassium leaching from muriate of potash in a tropical peat soil using clinoptilolite zeolite, forest litter compost, and chicken litter biochar - Krishnan, Kavinraj; Ngerong, Audrey Awing; Ahim, Karen; Ahmed, Osumanu Haruna; Ali, Maru; Omar, Latifah; Musah, Adiza Alhassan (MDPI, 2021)
Using muriate of potash (MOP) as a source of potassium (K) is a cost-effective method for crop production in tropical peat soils. However, exchangeable K commonly leaches from tropical peat soils because of high rainfall and a lack of clay to retain this cation. Potassium retention as exchangeable K could inhibit K loss through leaching to increase K availability. Clinoptilolite zeolite (CZ), forest litter compost (FLC), and chicken litter biochar (CLB) can be used to retain K from MOP in tropical peat soils for crop use because of the high affinity of CZ, FLC, and CLB for K ions. These approaches can be used as innovative and sustainable alternatives for the frequently used lime (CaCO3). However, information on using CZ, FLC, and CLB for MOP K retention is limited. Thus, CZ, FLC, and CLB were tested in a leaching study to determine their effects on MOP K retention in tropical peat soil. The use of CZ and FLC at rates of 100% and 75% of the recommended rate for pineapple cultivation (a commonly grown fruit crop in tropical peat soils in Malaysia) improved the K availability, pH, and CEC of the peat soil because of the high CEC of CZ and the humic substances (humic acids, fulvic acids, and humin) of FLC, which have a high affinity for K ions. The CLB did not improve K retention because of the competition between K, Ca, Mg, and Na ions, which are inherently high in this soil amendment. Instead of liming, which only replaces a few of the leached cations, such as calcium, the results of this study suggest an alternative method of retaining peat cations, such as K, that reduce peat acidity. This alternative method of retaining peat soil cations, especially K ions, is a practical and sustainable approach for improving peat soil productivity.